2021
DOI: 10.1002/jat.4261
|View full text |Cite
|
Sign up to set email alerts
|

Structural binding perspectives of common plasticizers and a flame retardant, BDE‐153, against thyroxine‐binding globulin: potential for endocrine disruption

Abstract: The human exposure to diverse endocrine‐disrupting chemicals (EDCs) has increased dramatically over several decades with very adverse health effects. Plasticizers and flame retardants constitute important classes of EDCs interfering in endocrine physiology including the thyroid function. Thyroxine (T4) is an important hormone regulating metabolism and playing key roles in developmental processes. In this study, six phthalate and nonphthalate plasticizers and one flame retardant (BDE‐153) were subjected to stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…PBDEs can also compete with T4 to bind with thyroxin-binding globulin and transthyretin, which transport thyroid hormones and prolong their half-life, and thyroid hormone receptor alpha and thyroid hormone receptor beta, which are thyroid hormone nuclear receptors responsible for the transcription of genes [66,70,71]. This will decrease T4 levels in the blood and cause thyroid gland hyperactivity as a feedback response [72], similar to our review's findings.…”
Section: Hormonal Healthsupporting
confidence: 82%
See 1 more Smart Citation
“…PBDEs can also compete with T4 to bind with thyroxin-binding globulin and transthyretin, which transport thyroid hormones and prolong their half-life, and thyroid hormone receptor alpha and thyroid hormone receptor beta, which are thyroid hormone nuclear receptors responsible for the transcription of genes [66,70,71]. This will decrease T4 levels in the blood and cause thyroid gland hyperactivity as a feedback response [72], similar to our review's findings.…”
Section: Hormonal Healthsupporting
confidence: 82%
“…Thyroid hormones exert their influence in the body at extremely low doses and are maintained through complex feedback mechanisms such that interactions of even low doses of PBDEs can cause disruptions in homeostasis through multiple known pathways [63][64][65][66]. For example, PBDEs and their metabolites can alter thyroid hormones by their interaction with deiodinases, which are enzymes that help in the synthesis of T3 from T4, by competing with T4 to bind at the active site [67].…”
Section: Hormonal Healthmentioning
confidence: 99%
“…Furthermore, metabolites of DEHA were shown to induce cytotoxicity in murine L929 Cell Line [ 35 ]. In our recent in silico study, we also reported potential thyroid dysregulation by non-phthalate alternate plasticizers, such as DINCH, DEHA, ATBC, etc., because of interactions with thyroxine-binding globulin [ 36 ]. All these above and other limited evidences point to the potential health risks of these emerging environmental contaminants, which is a serious cause of concern.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al reported the docking studies of PBDE structural analogues (hydroxylated PBDEs) with TR [ 63 ]. Similarly, in our previous study, we reported that BDE-153 structurally interacts with thyroxine binding globulin (TBG) [ 52 ]. In another study, we reported the binding of BDE-47, BDE-99, and their structural analogues with TBG [ 51 ].…”
Section: Discussionmentioning
confidence: 70%
“…PBDEs share their chemical structural resemblance with thyroid hormones, and hence have the potential to interfere with thyroid hormone action. The possible mechanisms include competitive binding with thyroid hormone receptors (TRα) and thyroid hormone transport proteins [ 49 , 50 , 51 , 52 ] and an increase in metabolism and clearance of T4 [ 53 ]. Numerous studies have reported that PBDEs interfere with T4 transport causing thyroid dysfunction [ 50 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%